2018
DOI: 10.1186/s12882-018-1090-3
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in autosomal dominant polycystic kidney disease: experimental hypothesis or clinical fact?

Abstract: BackgroundAutosomal dominant polycystic kidney disease (ADPKD) accounts for 8–10% of end-stage chronic kidney disease (CKD) patients worldwide. In the last decade, the advanced knowledge in genetics and molecular pathobiology of ADPKD focused some aberrant molecular pathways involved in the pathogenesis of the disease leading to controlled clinical trials aimed to delay its progression with the use of mTOR inhibitors, somatostatin or tolvaptan. Preclinical studies suggests an effective role of metformin in ADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
(25 reference statements)
1
18
0
1
Order By: Relevance
“…One retrospective, case-control study, which selected 7 diabetic ADPKD patients treated with Metformin and 7 matched non-diabetic ADPKD controls, evaluated the effect of Metformin on renal function progression during a 3 year follow-up. An overall crude loss of eGFR of – 0.9 ml/min/1.73m 2 estimated by a linear mixed model at 36 months was reported in the Metformin group [28]. Our ITT analysis was in line with these results, as we found a change in mean eGFR of – 1.57 ml/min/1.73 m 2 after 24 months of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…One retrospective, case-control study, which selected 7 diabetic ADPKD patients treated with Metformin and 7 matched non-diabetic ADPKD controls, evaluated the effect of Metformin on renal function progression during a 3 year follow-up. An overall crude loss of eGFR of – 0.9 ml/min/1.73m 2 estimated by a linear mixed model at 36 months was reported in the Metformin group [28]. Our ITT analysis was in line with these results, as we found a change in mean eGFR of – 1.57 ml/min/1.73 m 2 after 24 months of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, we found that AMPK activation via Metformin had no effect on cell proliferation. Although Metformin was suggested to have beneficial effects on disease progression 27 , the effect of Metformin on cell proliferation and cyst growth has been brought into question by another recent study 28 . Additionally, differences in concentration or time frame of compound treatment could account for the lack of activity observed.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin was first clinically used as a hypoglycemic agent (18,19). Subsequent studies demonstrated that metformin had different effects on various tissues and systems (29,30). Metformin was revealed to prevent the sevoflurane-induced apoptosis of neurons, which was reversed by a specific S1P1 antagonist (31).…”
Section: Discussionmentioning
confidence: 99%